1980
DOI: 10.1007/bf00355454
|View full text |Cite
|
Sign up to set email alerts
|

Human operator dynamics in manual tracking systems with auditory input

Abstract: Response characteristics of human operators in manual pursuit tracking with auditory input are investigated. The human operator hears in his left ear a sound whose frequency varies in proportion to an external random signal. At the same time, he hears in his right ear another sound whose frequency varies in proportion to the angle of a control lever of a potentiometer. The operator controls the angle of the lever so that the frequencies, of the sounds in both ears remain as close as possible. The dynamics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For example, Hill (1970) compared the performance of subjects when tracking visual and tactile displays and, in contrast to earlier results (Seeley and Bliss 1966), found that the error variance was 40% lower when visual displays were used, and that longer time delays were associated with tactile inputs. Auditory (Mirchandani 1972;Takashima et al 1980) and kinesthetic inputs (Neilson 1972) have also been used to determine the response characteristics of the human operator in tracking situations. It appears that the more successful non-visual tracking systems have relied on compensatory rather than pursuit tracking, presumably because the limits of discrimination make it difficult in some sensory modalities to follow both the target and current response simultaneously (Hammerton 1981).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hill (1970) compared the performance of subjects when tracking visual and tactile displays and, in contrast to earlier results (Seeley and Bliss 1966), found that the error variance was 40% lower when visual displays were used, and that longer time delays were associated with tactile inputs. Auditory (Mirchandani 1972;Takashima et al 1980) and kinesthetic inputs (Neilson 1972) have also been used to determine the response characteristics of the human operator in tracking situations. It appears that the more successful non-visual tracking systems have relied on compensatory rather than pursuit tracking, presumably because the limits of discrimination make it difficult in some sensory modalities to follow both the target and current response simultaneously (Hammerton 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The slalom maneuver is one of the tasks defined as an element often used for assessing the handling qualities of aircraft [ADS-33D-PRF (ADS 1996)]. The tracking task is a maneuver convenient for later evaluation (Gittleman et al 1992;Ito and Ito 1975;Takashima et al 1980). The slalom parameters were adopted to the maneuverability of the particular UAV, so the task completion was possible with the set criteria (Freeman et al 2000;Kopyt et al 2017).…”
Section: Hardwarementioning
confidence: 99%
“…Information about the human operator's performance when controlling a robot or simulated "vehicle" is usually presented visually (McRuer 1980), although tactile (Hill 1970;Schmid and Bekey 1978), auditory (Mirchandani 1972;Takashima et al 1980) and kinaesthetic (Jagacinski et al 1979(Jagacinski et al , 1983) displays have also been used to convey error information to the operator. Visual and tactile error signals result in similar performance if the signal fed back to the operator consists of the error (i.e.…”
Section: Introductionmentioning
confidence: 99%